Reducing global poverty the case for asset accumulation - Moser, Caroline O. N.; ProQuest (Firm) (Washington, D.C. : Brookings Institution Press, 2007)
"Provides a set of case studies of asset-building projects around the globe aimed at designing and implementing public policies that will increase the capital assets of the poor. Highlights the ways in which poor households and communities can move out of poverty through longer-term accumulation of capital assets"--Provided by publisher.
Introduction / Caroline Moser -- Intergenerational asset accumulation and poverty reduction in Guayaquil, Ecuador, 1978-2004 / Caroline Moser and Andrew Felton -- Learning from asset-based approaches to poverty / Michael R. Carter -- The stages-of-progress methodology and results from five countries / Anirudh Krishna -- Asset accumulation policy and poverty reduction / Caroline Moser -- Addressing vulnerability through asset building and social protection / Sarah Cook -- Social protection and asset accumulation by the middle class and the poor in Latin America / Andres Solimano -- Building natural resource-based assets in southern Africa : workable scenarios / Paula Nimpuno-Parente -- Protecting land rights in post-tsunami and postconflict Aceh, Indonesia / Lilianne Fan -- Hurricane Katrina : impact on assets and asset-building approaches to poverty reduction / Amy Liu -- Gangs, violence, and asset building / Dennis Rodgers -- Beyond microfinance / Vijay Mahajan -- Using microinsurance and financial education to protect and accumulate assets / Monique Cohen and Pamela Young -- Migrant foreign savings and asset accumulation / Manuel Orozco -- Transnational communities of the United States and Latin America / Hector Cordero-Guzman and Victoria Quiroz-Becerra -- Gender and transnational asset accumulation in El Salvador / Sarah Gammage -- Claiming rights : citizenship and the politics of asset distribution / Clare Ferguson, Caroline Moser, and Andy Norton.
This volume grew out of the Brookings Institution-Ford Foundation Workshop on Asset-based Approaches to Poverty Reduction in a Globalized Context, held in Washington, D.C., on June 27-28, 2006, led by Caroline Moser, and co-hosted by the Ford Foundation.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Poverty -- Developing countries -- Congresses; Poverty -- Government policy -- Developing countries -- Congresses; Poor -- Developing countries -- Finance, Personal -- Congresses; Microfinance -- Developing countries -- Congresses; Developing countries -- Social policy -- Congresses; Electronic books